A novel plasmid‐based experimental system in Saccharomyces cerevisiae that enables the introduction of 10 different plasmids into cells - Geyao Dong; Tsuyoshi Nakai; Tetsuo Matsuzaki (FEBS Open Bio)
The budding yeast Saccharomyces cerevisiae is commonly used as an expression platform for the production of valuable compounds. Yeast‐based genetic research can uniquely utilize auxotrophy in transformant selection: auxotrophic complementation by an auxotrophic marker gene on exogenous DNA (such as plasmids). However, the number of required auxotrophic nutrients restricts the number of plasmids maintained by the cells. We, therefore, developed novel Δ10 strains that are auxotrophic for 10 different nutrients and new plasmids with two multiple cloning sites and auxotrophic markers for use in Δ10 strains. We confirmed that Δ10 strains were able to maintain 10 types of plasmids. Using plasmids encoding model proteins, we detected the co‐expression of 17 different genes in Δ10 cell lines. We also constructed Δ9 strains that exhibited auxotrophy for nine nutrients and increased growth compared to Δ10. This study opens a new avenue for the co‐expression of a large number of genes in eukaryotic cells.